The role of perennation traits in plant community soil frost stress responses - Lubbe, Frederick Curtis; Henry, Hugh A L (Annals of botany, 2020)
BACKGROUND AND AIMS: Herbaceous plants can survive periods of prolonged freezing as below-ground structures or seed, which can be insulated from cold air by soil, litter or snow. Below-ground perennial structures vary in both form and their exposure to soil frost, and this structural variation thus may be important in determining the responses of plant communities to frost stress. METHODS: We conducted a suite of snow removal experiments in a northern temperate old field over 3 years to examine the relative freezing responses of different plant functional groups based on below-ground perennation traits. A litter removal treatment was added in the third year. Species-level percentage cover data were recorded in May, June and September then pooled by functional group. KEY RESULTS: Snow removal decreased total plant cover, and this response was particularly strong and consistent among years for tap-rooted and rhizomatous species. The snow removal responses of cover for plants with root buds and new recruits from seed varied from positive to negative among years. The cover of rootstock plants consistently increased in response to snow removal. Rhizomatous species were generally the most vulnerable to litter removal. CONCLUSIONS: This study is the first to explore the effects of variation in frost severity on the responses of different plant perennation trait functional groups. The responses of herbaceous species to frost may become increasingly important in northern temperate regions in the coming decades as a result of declining snow cover and increasing temperature variability. Our results reveal substantial variation in responses among perennation trait functional groups, which could drive changes in species abundance in response to variation in soil frost.
Keywords: rostliny; Plants; frost; zmrazování; perennation; snow removal; herbaceous; Freezing; sníh; Snow; půda; Below-ground; taproot; community; roční období; Seasons; life form; Soil